Primadeva Utama Catering Makassar's Business Development Strategy - Zhafirin, Ghaza Naufal; Siswhara, Gita; Waluya, Bagja (Universitas Pendidikan Indonesia, 2019)
This study aims to determine how the strategy that must be carried out by Primadeva Utama Catering is to develop business in the face of increasingly fierce catering industry competition in the city of Makassar. This research uses quantitative descriptive methods. The data obtained were then analyzed using IFAS matrices, EFAS matrices, IE matrices, SWOT matrices, and QSPM matrices. The IFAS and EFAS matrix analysis results show that the internal factors with the highest value are the taste and portion of food, while for external factors is a broad target market, ranging from the lower middle class to the upper class. Based on the results of the IE matrix analysis, Primadeva Utama Catering is in quadrant five. This position shows a good growth strategy used by the company is concentration through horizontal integrity, which is innovating or modifying products and utilizing economies of scale in profits in production and marketing. With this in mind, the authors recommend 7 alternative strategies for developing the Primadeva Utama Catering business based on the results of the SWOT matrix analysis. Through data processing using QSPM, it can be seen that the alternative is a priority strategy to innovate on a price menu and flexible service package by considering consumer demand trends, these trends are a form of service events and consumer purchasing power with Stas. a value of 7.17.Â